2019
DOI: 10.1002/etc.4325
|View full text |Cite
|
Sign up to set email alerts
|

Passive sampling of pesticides and polychlorinated biphenyls along the Quequén Grande River watershed, Argentina

Abstract: Water monitoring is of great importance, especially for water bodies in agricultural or industrial areas. Grab sampling is a widely used technique for aquatic monitoring but represents only a snapshot of the contaminant levels at a specific point in time. Passive sampling, on the other hand, is an integrative technique that provides an average concentration of contaminants representative of its deployment period. Thus, the current contamination by organochlorine pesticides, polychlorinated biphenyls (PCBs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Monitoring spatial and temporal trends River waters PAHs; PCBs; pesticides; phthalates SR alongside Speedisk PSDs were used to monitor the spatial and temporal variation in sources, occurrence, concentrations and fate of a range of HOCs within various river catchments. [191][192][193][194][195]207] Coastal waters PAHs; PCBs; pesticides SR and other PSDs (LDPE, Chemcatcher ® and SPMD) were deployed in various exposures at coastal sites to investigate temporal and spatial trends in the concentration of a range of target HOCs and to screen for the occurrence of HOCs and use of detection frequency to inform a fugacity model.…”
Section: Coastal Watersmentioning
confidence: 99%
“…Monitoring spatial and temporal trends River waters PAHs; PCBs; pesticides; phthalates SR alongside Speedisk PSDs were used to monitor the spatial and temporal variation in sources, occurrence, concentrations and fate of a range of HOCs within various river catchments. [191][192][193][194][195]207] Coastal waters PAHs; PCBs; pesticides SR and other PSDs (LDPE, Chemcatcher ® and SPMD) were deployed in various exposures at coastal sites to investigate temporal and spatial trends in the concentration of a range of target HOCs and to screen for the occurrence of HOCs and use of detection frequency to inform a fugacity model.…”
Section: Coastal Watersmentioning
confidence: 99%
“…The average concentration of β -endosulfan in the south Indian rivers was lower than that of other rivers such as Brahmaputra and Hooghly ( Chakraborty et al, 2016a , Khuman and Chakraborty, 2019 ) but comparable with Gomti in India ( Malik et al, 2009 ) and Maozhou, Guanlan, Buji, Longgan and Pingshan rivers of China ( Qiu et al, 2021 ). The levels were lower than levels from Chenab ( Eqani et al, 2012 ) and Ravi ( Baqar et al, 2018 ) rivers in Pakistan and Pampanga River, Philippines ( Navarrete et al, 2018 ) but were higher than levels observed in Quequén Grande River, Argentina ( Silva‐Barni et al, 2019 ) ( Table S5 ).…”
Section: Resultsmentioning
confidence: 76%
“…Induction and accumulation of UV-absorbing compounds (UACs, such as mycosporinelike amino acids among others), flavonoids, or carotenoids can help some microalgae/macroalgae species to cope with the pro-oxidant UVR effects (Marcoval et al 2007;Navarro et al 2008), while chemical stress can also produce the induction of both enzymatic and non-enzymatic antioxidant responses (Bhargava et al 2007;Wang et al 2011). Synthetic pesticides used in agriculture could reach aquatic environments near or far from sources such as estuarine and coastal waters (Munaron et al 2012;Silva-Barni et al 2019). In this sense, most of the studies on the tolerance of microalgae to pesticides are focused on herbicides due to their action on the photosynthetic system (Jamers and De Coen 2010;Lozano et al 2014) and mainly on freshwater species (Nestler et al 2012;Baruah and Chaurasia 2020).…”
Section: Graphical Abstractmentioning
confidence: 99%